1969
DOI: 10.1530/jrf.0.0200491
|View full text |Cite
|
Sign up to set email alerts
|

Control of Luteal Function During Early Pregnancy in the Guinea-Pig

Abstract: Summary. Removal of the conceptuses (decidua+embryos) from the uterus of the guinea-pig between the 9th and 15th days after mating allowed the recurrence of oestrus at, or only slightly after, the time it would have occurred had not fertile mating taken place. The transfer of a single 6-day blastocyst to the uterus of unmated cycling animals resulted in pregnancy in three of six animals in which the cycles of the host and donor were synchronized. Normal development was never observed after transfer of 9-to 11-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Placental contribution to luteal maintenance must also be considered. If an 11-12-day embryo, but not a 9-10-day embryo, is transplanted to a normal guinea-pig, then oestrus is delayed (Bland & Donovan, 1969), suggesting that a placental anti-luteolysin acts between Days 12 and 25 of pregnancy to maintain corpora lutea. In the present study the pregnancies were less sensitive to oestrogen at Days 10 and 11 than at Days 17 and 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Placental contribution to luteal maintenance must also be considered. If an 11-12-day embryo, but not a 9-10-day embryo, is transplanted to a normal guinea-pig, then oestrus is delayed (Bland & Donovan, 1969), suggesting that a placental anti-luteolysin acts between Days 12 and 25 of pregnancy to maintain corpora lutea. In the present study the pregnancies were less sensitive to oestrogen at Days 10 and 11 than at Days 17 and 18.…”
Section: Discussionmentioning
confidence: 99%
“…However, the factors involved in maintaining pregnancy are little understood. The involvement of an anti-luteolysin in the maintenance of the corpora lutea has been proposed (Bland & Donovan, 1969;Maule Walker & Poyser, 1974). Blatchley, Maule Walker & Poyser (1975) suggested that inhibition of oestradiol release early in pregnancy may be important.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an ovariectomy at mid-pregnancy or the later trimester of pregnancy does not disrupt the process of pregnancy in several mammals, including humans (Csapo et al 1972), monkeys (Albrecht et al 2000), guinea pigs (Bland & Donovan 1969), and/or mares (Hinrichs et al 1987), whose progestin and estrogen are supplied by other tissues such as the placenta. In ovariectomized mares, a daily single injection of progesterone is sufficient to establish and maintain pregnancy after embryo transfer (Hinrichs et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Observations were made on Days 5, 9 and 20 of pregnancy (in this species, pregnancy lasts an average of 63 days; Rowlands, 1949). By Day 5, luteinization is complete and a fully functional corpus luteum is present (Bland & Donovan, 1969;Challis et ai, 1971;Hilliard, 1973) and implantation has not taken place (Blandau, 1949). Studies on clomiphene-treated animals at this time should give evidence of interference with the preimplantation uterus and normal CL formation and function.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on Day 9, when implan¬ tation has taken place (Days 6-7, Blandau, 1949) and implantation swellings are clear on the uterus, should give evidence for interference with implantation, decidualization and CL main¬ tenance. Between Days 9 and 20, progesterone becomes essential for pregnancy maintenance (Days 11-14, Loeb & Hesselburg, 1917;Deanesly, 1960Deanesly, , 1963bCsapo et ai, 1981), the conceptus produces a luteotrophic substance (Days 12-25, Bland & Donovan, 1969;Blatchley et ai, 1975;Antonini et ai, 1976;Poyser & Maule Walker, 1979) and the switch of progesterone secretion from CL to placenta takes place from Day 15, (Deanesly, 1960;Heap & Deanesly, 1966 (Orkzyk et al, 1979).…”
Section: Introductionmentioning
confidence: 99%